Preliminary thoughts on the relationship between knowledge creation and obsolescence in an information-based economy - Kenney, Martin (Nova Economia, 2013)
The new electronics technologies are propelling a transformation in value creation from being based on physical work to being based on knowledge. While the economy thus created is based on innovation, its corollary is an acceleration in obsolescence. Some products such as personal computers are now on a three-month product cycle, demonstrating that even as value is being created more quickly, it also being destroyed more quickly. In the case of software, the quintessential product of the Information Economy, obsolescence is also extremely rapid. Information and knowledge creation have already become the central pivot in capitalist economies and this is like to continue and even become more prevalent. Current descriptions of the economy emphasis its roots in information and/or knowledge, to this we might add that the economy is obsolescence-based.